Union Influence on Worker Education and Training in Canada in Tough Times - Livingstone, D W; Raykov, M (Just Labour, 2005)
This research has focused on re-analyzing data from previous large-scale Canadian surveys that include information on education and training activities and union status, as well as other demographic and organizational factors, most prominently the 1993 and 1997 Adult Education and Training Surveys. In contrast to some recent studies, we find that union status has had consistent positive individual-level effects in Canada on participation in adult education courses and employer-sponsored courses in general, and especially for women union members. In addition, our analysis of data from the 1998 national survey on informal learning finds that in this much more extensive form of learning, unionized workers are significantly more likely than non-unionized workers to participate in more directly empowering forms of knowledge including learning about workers’ rights and political issues.